LAMP MODIFICATION FROM HPLN TO LED TECHNOLOGY FOR SAVING ELECTRICAL ENERGY IN STREET LIGHTING - Rosdiana Rosdiana; Arya Wiyangga Pradana; Muhammad Muhammad; Mutammimul Ula (Universitas Mulia, 2023)
Energy Efficiency is a business that is carried out with the aim of reducing the amount of energy needed, in using an equipment or even an energy-related system. In its development in the field of lighting, LED (Light Emitting Diode) lamps are now starting to be used as lighting lamps for homes, industries and factories. In Indonesia, the use of LED lamps in lighting is still rarely used, because the price of LED lamps is quite expensive when compared to ordinary lamps. With the saving of electric power through the use of LED lights, the problem of operational costs will be easy to overcome. Indeed, the price of this LED lamp is a little expensive, but with the research on the comparison of the use of this LED lamp with HPL-N type lamps, the industry will consider using this LED lamp with a generally accepted application method to reduce energy expenditure. The previous conditions for Jalan Dolok Merawan used HPLN 250 Watt lamps with a handlebar angle of 24,920 ornaments, the resulting light intensity was 2189 Candela, the intensity of the resulting lighting was 97.94 Lux and has now been changed to make it more optimal to use 120 Watt LED type lights, the height of the pole used is 4 meterss with an ornament handlebar angle of 24.920, light intensity of 1242 Candella, lighting intensity of 55.33 lux. The results of this illumination intensity are in accordance with the standard determined by BSN SNI regarding Collector road class 3-7 Lux. The results achieved after the process of modifying HPL-N lamps to LEDs are that they can reduce the use of electrical energy in the lighting system and achieve efficiency for electric power consumption so that they can provide added value to the company in reducing the company's operational costs.